Sociodemographic and obstetric determinants associated with preeclampsia in pregnant women treated at the Carlos Monge Medrano Hospital in Juliaca - 2022 - Cosi Chura, Silvia Veronica; Condori Caira, Yuvy Guadalupe (Universidad Privada de Huancayo Franklin Roosevelt, 2023)
El objetivo es identificar los determinantes sociodemográficos y obstétricos asociados a preeclampsia en gestantes atendidas en el hospital Carlos Monge Medrano de Juliaca 2022. Como método, se utilizó un diseño de estudio de tipo correlacional, descriptivo, de corte transversal. Se aplicó el muestreo por conveniencia, y fueron seleccionadas 92 gestantes. La técnica empleada fue desarrollada en dos etapas, recolección de datos y encuesta. En conclusión, se identificó que los determinantes sociodemográficos y obstétricos se asocian a preeclampsia en gestantes atendidas en el hospital Carlos Monge Medrano de Juliaca ya que al realizar la media aritmética de los datos del nivel de significancia se obtuvo como resultado 0.0101, el mismo que es menor a 0.05.

The objective was to identify the sociodemographic and obstetric determinants associated with preeclampsia in pregnant women attended at the Carlos Monge Medrano hospital in Juliaca 2022. The method used was a cross-sectional, descriptive, correlational, descriptive study design. Convenience sampling was applied, and 92 pregnant women were selected. The technique used was developed in two stages, data collection and survey. In conclusion, it was identified that the sociodemographic and obstetric determinants are associated with preeclampsia in pregnant women attended at the Carlos Monge Medrano Hospital in Juliaca, since the arithmetic mean of the data at the significance level was 0.0101, which is less than 0.05.
Keywords: Determinantes sociodemográficos; Obstétricos; Preeclampsia; http://purl.org/pe-repo/ocde/ford#3.02.02